Preoccupations things artists do anyway: 111 artists reveal their obsessions - Lee Hong Hwee, Michael (Hong Kong Laiyan Projects & Studio Bibliothèque, 2008)
Things artists do is an exhibition/publication series of Studio Bibliothèque. It aims to address the gap amidst the onslaught of survey, thematic art shows and books by focusing on the being, consumption and activities of artists.
Donated by Prof. Dayang Nirvana Magdalena Yraola
Keywords: Artists; Artists -- Literary collections; Artists -- Asia; Artists -- Singapore